2015
DOI: 10.1038/sdata.2015.3
|View full text |Cite
|
Sign up to set email alerts
|

The pediatric template of brain perfusion

Abstract: Magnetic resonance imaging (MRI) captures the dynamics of brain development with multiple modalities that quantify both structure and function. These measurements may yield valuable insights into the neural patterns that mark healthy maturation or that identify early risk for psychiatric disorder. The Pediatric Template of Brain Perfusion (PTBP) is a free and public neuroimaging resource that will help accelerate the understanding of childhood brain development as seen through the lens of multiple modality neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 108 publications
2
54
0
Order By: Relevance
“…2011; Avants et al. 2015). While there is a general trend of decreasing CBF with age from childhood through adolescence, within the age range of the present cohort (7 to 17 years), aberrant neurodevelopment can manifest as either increased or decreased CBF depending on the developmental trajectory of the particular brain regions of interest.…”
Section: Discussionmentioning
confidence: 99%
“…2011; Avants et al. 2015). While there is a general trend of decreasing CBF with age from childhood through adolescence, within the age range of the present cohort (7 to 17 years), aberrant neurodevelopment can manifest as either increased or decreased CBF depending on the developmental trajectory of the particular brain regions of interest.…”
Section: Discussionmentioning
confidence: 99%
“…The non-rigid transformation between the template and each individual mouse was estimated using the open source Advanced Normalization Tools (ANTs) package 34 that was then used to propagate the regional labels to each subject. Cleaning of the bold fMRI data was performed using tools available in ANTsR 35 – a statistical and visualization interface between ANTs and the R statistical project. fMRI preprocessing consisted of motion correction 36 , band pass filtering (freq.…”
Section: Methodsmentioning
confidence: 99%
“…To date, however, only a handful of nuclear medicine studies (Chiron et al, 1992;Chugani, 1998;Takahashi et al, 1999;Wintermark et al, 2004) reported developmental changes in CBF, CMRglu and CMRO 2 , suggesting a general peak around 5-8 years followed by tapering to adult levels throughout adolescence. Similar developmental trajectories of resting CBF have recently been shown by ASL perfusion MRI studies (Avants et al, 2015;Biagi et al, 2007;Satterthwaite et al, 2014;Taki et al, 2011aTaki et al, , 2011bWang and Licht, 2006;Wang et al, 2003). Detailed region and sex specific developmental trajectories of CBF have been revealed after the effect of age-related variations in cortical structure was adjusted (Satterthwaite et al, 2014;Taki et al, 2011aTaki et al, , 2011b.…”
Section: Developmental Trajectories Of Cbf and Cmro 2 At Baselinementioning
confidence: 51%
“…Quantitative CBF were calculated using a standard model taking into account age and gender dependent blood T1 changes (Jain et al, 2012), while assuming a labeling efficiency of 0.85. PCASL images were coregistered to the brainextracted structural T1 MPRAGE scan in each individual subjects, followed by normalization to the study specific pediatric template in the MNI space constructed using the Advanced Normalization Tools (ANTs) (Avants et al, 2015). Images were subsequently spatially smoothed using a Gaussian kernel (FWHM: 8 × 8 × 8 mm).…”
Section: Working Memory Fmri With Concurrent Cbf and Boldmentioning
confidence: 99%
See 1 more Smart Citation